2018
DOI: 10.1016/j.jgr.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented black ginseng on wound healing mediated by angiogenesis through the mitogen-activated protein kinase pathway in human umbilical vein endothelial cells

Abstract: BackgroundFermented black ginseng (FBG) is produced through several cycles of steam treatment of raw ginseng, at which point its color turns black. During this process, the original ginsenoside components of raw ginseng (e.g., Re, Rg1, Rb1, Rc, and Rb2) are altered, and less-polar ginsenosides are generated (e.g., Rg3, Rg5, Rk1, and Rh4). The aim of this study was to determine the effect of FBG on wound healing.MethodsThe effects of FBG on tube formation and on scratch wound healing were measured using human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This disruption mainly manifests as the excessive accumulation of lipids, downexpression of NO, and enhanced expression of ET‐1 (King et al., 2016). Several studies have indicated the protective effect of ginseng on the endothelial function (In‐Ho et al., 2018; Jovanovski et al., 2014; Park et al., 2018). In addition, the phenolic acid components from other plants have demonstrated regulatory potential for endothelial function (Del Bo et al., 2016; Tang et al., 2018; Toma et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This disruption mainly manifests as the excessive accumulation of lipids, downexpression of NO, and enhanced expression of ET‐1 (King et al., 2016). Several studies have indicated the protective effect of ginseng on the endothelial function (In‐Ho et al., 2018; Jovanovski et al., 2014; Park et al., 2018). In addition, the phenolic acid components from other plants have demonstrated regulatory potential for endothelial function (Del Bo et al., 2016; Tang et al., 2018; Toma et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The wound healing activity of fermented black ginseng in human umbilical vein endothelial cells was mediated by angiogenesis through the MAP kinase pathway and enhanced the tube formation in HUVECs and migration in HaCaT cells was discussed [153]. Fermented black ginseng could stimulate the phosphorylation of p38 and extracellular signal-regulated kinase in HaCaT cells.…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…Fermented black ginseng could stimulate the phosphorylation of p38 and extracellular signal-regulated kinase in HaCaT cells. Moreover, mice treated with 25 mg/mL exhibited faster wound closure in the experimental cutaneous wounds model [153].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…Ginsenoside Rg3, ginsenoside Rk1, and ginsenoside Rg5 contents in BG are up to 30 times higher than those in RG [ 6 , 7 ]. Many studies have reported that ginseng has various functions, including hypoglycemic action, anti-cancer effects, anti-obesity effects, antioxidant effects, and liver function improvement [ 8 , 9 ]. However, through multiple steaming cycles the ginseng is carbonized.…”
Section: Introductionmentioning
confidence: 99%